Contingent trade policy and economic efficiency - Phillip McCalman; Frank Stähler; Gerald Willmann (Kiel Institute for the World Economy (IfW), 2013)
This paper develops an efficiency theory of contingent trade policies. We model the competition for a domestic market between one domestic and one foreign firm as a pricing game under incomplete information about production costs. The cost distributions are asymmetric because the foreign firm incurs a trade cost to serve the domestic market. We show that the foreign firm prices more aggressively to overcome its cost disadvantage. This creates the possibility of an inefficient allocation, justifying the use of contingent trade policy on efficiency grounds. Despite an environment of asymmetric information, contingent trade policy that seeks to maximize global welfare can be designed to avoid the potential inefficiency. National governments, on the other hand, make excessive use of contingent trade policy due to rent shifting motives. The expected inefficiency of national policy is larger (smaller) for low (high) trade costs compared to the laissez-faire case. In general, there is no clear ranking between the laissez-faire outcome and a contingent national trade policy.
Keywords: F12; F13; 330; Contingent Trade Policy; Efficiency